Modeling to inform economy-wide pandemic policy: Bringing epidemiologists and economists together - Michael Darden; David Dowdy; Lauren Gardner; Barton Hughes Hamilton; Karen A. Kopecky; Melissa Marx; Nicholas W. Papageorge; Daniel Polsky; Kimberly Powers; Elizabeth Stuart; Matthew Zahn (Federal Reserve Bank of Atlanta, 2021)
Facing unprecedented uncertainty and drastic trade-offs between public health and other forms of human well-being, policymakers during the Covid-19 pandemic have sought the guidance of epidemiologists and economists. Unfortunately, while both groups of scientists use many of the same basic mathematical tools, the models they develop to inform policy tend to rely on different sets of assumptions and, thus, often lead to different policy conclusions. This divergence in policy recommendations can lead to uncertainty and confusion, opening the door to disinformation, distrust of institutions, and politicization of scientific facts. Unfortunately, to date, there have not been widespread efforts to build bridges and find consensus or even to clarify sources of differences across these fields, members of whom often continue to work within their traditional academic silos. In response to this "crisis of communication," we convened a group of scholars from epidemiology, economics, and related fields (such as statistics, engineering, and health policy) to discuss approaches to modeling economy-wide pandemics. We summarize these conversations by providing a consensus view of disciplinary differences (including critiques) and working through a specific policy example. Thereafter, we chart a path forward for more effective synergy among disciplines, which we hope will lead to better policies as the current pandemic evolves and future pandemics emerge.
Keywords: C8; H0; I1; J0; 330; economics; epidemiology; public health; Covid-19; behavior modeling; health outcomes; health-wealth tradeoffs